PERAN GURU DALAM PERKEMBANGAN MORAL PESERTA DIDIK SDN 1 TONJONG - Hayklah Aji Maulana; Muhamad Candra Kurniawan; Nurkholis (PT. Hasba Edukasi Mandiri, 2025)
As an essential part of the teaching process, teachers have a dual role: they not only teach students but also help them reach their potential, provide choices, and guide them in learning. This study aims to provide an in-depth overview of the role of teachers in the moral development of elementary school students at SDN 1 Tonjong. This study uses a descriptive qualitative approach that utilizes interviews and observations. This study provides an in-depth overview of the role of teachers in the moral development of fifth-grade elementary school students at SDN 1 Tonjong. This study found that moral education not only improves students' ability to interact with others but also helps them develop values such as responsibility, tolerance, and collaboration. Moral development is crucial for character formation in students, especially in elementary school. The results of this study indicate that teachers play a crucial role in building students' morality through lessons related to good moral examples and classroom rules.